2016
DOI: 10.1016/j.ejbt.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The exopolysaccharides biosynthesis by Candida yeast depends on carbon sources

Abstract: a b s t r a c t 7 a r t i c l e i n f o 8 Available online xxxx 12 13 14 15 16 17Background: The exopolysaccharides (EPS) produced by yeast exhibit physico-chemical and rheological 18 properties, which are useful in the production of food and in the cosmetic and pharmaceutical industries as 19 well. The effect was investigated of selected carbon sources on the biosynthesis of EPS by Candida famata and 20 Candida guilliermondii strains originally isolated from kefirs. 21 Results: The biomass yields were depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…The effects of simultaneous expression of multiple cellulases on the growth of Y. lipolytica was investigated by plotting the turbidity obtained from a Bioscreen C growth assay. Previously, the Bioscreen C instrument has been used to monitor microbial growth curve in terms of optical density of bacteria (Franden et al, 2009, 2013; Wang et al, 2014b) and yeast (Bom et al, 2001; Jung et al, 2015; Gientka et al, 2016). Y. lipolytica transformants expressing single cellulases were similar to their parent strain Po1g (EV) during the exponential growth phase and only show slight differences during the late growth phase (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of simultaneous expression of multiple cellulases on the growth of Y. lipolytica was investigated by plotting the turbidity obtained from a Bioscreen C growth assay. Previously, the Bioscreen C instrument has been used to monitor microbial growth curve in terms of optical density of bacteria (Franden et al, 2009, 2013; Wang et al, 2014b) and yeast (Bom et al, 2001; Jung et al, 2015; Gientka et al, 2016). Y. lipolytica transformants expressing single cellulases were similar to their parent strain Po1g (EV) during the exponential growth phase and only show slight differences during the late growth phase (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Bullera, Candida, Cryptococcus, Debaryomyces, Lipomyces, Pichia, Pseudozyma, Rhodotorula, and Sporobolomyces (Rusinova-Videva et al 2010). The EPS produced by Candida yeast exhibited physicochemical and rheological properties which are useful in food, cosmetic, and pharmaceutical industries (Gientka et al 2016). Probiotic yeasts viz.…”
Section: Introductionmentioning
confidence: 99%
“…Many research put forward hypotheses that carbon sources as a main precursor for EPS production had the highest effect on the polysaccharide's properties and supported the high quantity of polysaccharide. Various research studies were carried out to investigate the effect of the carbon and nitrogen sources on polysaccharides production (Gientka, Bzducha‐Wróbel, Stasiak‐Różańska, Bednarska, & Błażejak, 2016; Khani et al., 2016). Khani et al., 2016 (Khani et al., 2016) stated that EPS production was stimulated by the high content of glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Khani et al., 2016 (Khani et al., 2016) stated that EPS production was stimulated by the high content of glucose. A study done by Gientka et al, 2016 (Gientka et al., 2016) revealed that, of all substrates used, carbon source significantly enhanced the yeast polysaccharide. Maalej et al., 2014 stated starch was discovered to be preferred over other carbon sources for EPS by Pseudomonas stutzeri AS22.…”
Section: Resultsmentioning
confidence: 99%